2014
DOI: 10.1093/toxsci/kfu066
|View full text |Cite
|
Sign up to set email alerts
|

The γH2AX Assay for Genotoxic and Nongenotoxic Agents: Comparison of H2AX Phosphorylation with Cell Death Response

Abstract: DNA double-strand breaks (DSBs) and blocked replication forks resulting from bulky adducts and inhibitors of replication activate the DNA damage response (DDR), a signaling pathway marked by phosphorylation of histone 2AX (H2AX). The phosphorylated form, γH2AX, accumulates at the site of the damage and can be visualized as foci by immunocytochemistry. The objective of this study was to assess if γH2AX is a reliable biomarker for genotoxic exposures. To this end, we selected 14 well-known genotoxic compounds an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
81
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 58 publications
4
81
0
Order By: Relevance
“…Phosphorylation of histone H2AX at serine 139 (producing γ‐H2AX) is a well‐established biomarker of DNA damages, particularly DNA double‐strand breaks (Pilch et al, ; Rogakou, Pilch, Orr, Ivanova, & Bonner, ). γ‐H2AX has been used in multiple scientific fields, e.g., in vitro assessment of preclinical drugs and genotoxicity screening for chemical materials (Khoury, Zalko, & Audebert, ; Nikolova et al, ; Watters, Smart, Harvey, & Austin, ), and is rapidly accumulated over a large region of chromatin surrounding double‐strand breaks (Rogakou, Boon, Redon, & Bonner, ), leading to aggregation of repair proteins; this process can be microscopically detected by immunofluorescence and immunohistochemistry using specific primary antibodies (Redon et al, ). Therefore, immunostaining of γ‐H2AX is expected to be applied as a useful tool to predict in vivo genotoxicity of chemicals (Nagelkerke & Span, ; Thompson et al, ; Toyoda et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of histone H2AX at serine 139 (producing γ‐H2AX) is a well‐established biomarker of DNA damages, particularly DNA double‐strand breaks (Pilch et al, ; Rogakou, Pilch, Orr, Ivanova, & Bonner, ). γ‐H2AX has been used in multiple scientific fields, e.g., in vitro assessment of preclinical drugs and genotoxicity screening for chemical materials (Khoury, Zalko, & Audebert, ; Nikolova et al, ; Watters, Smart, Harvey, & Austin, ), and is rapidly accumulated over a large region of chromatin surrounding double‐strand breaks (Rogakou, Boon, Redon, & Bonner, ), leading to aggregation of repair proteins; this process can be microscopically detected by immunofluorescence and immunohistochemistry using specific primary antibodies (Redon et al, ). Therefore, immunostaining of γ‐H2AX is expected to be applied as a useful tool to predict in vivo genotoxicity of chemicals (Nagelkerke & Span, ; Thompson et al, ; Toyoda et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The proteins, such as c-H2AX, ATM, CDKN1A, and TP53, involved in the early steps of the cellular response in sensing DNA damage and controlling progression, have been proposed as the top group of candidate biomarkers (Marchetti et al, 2006). Due to the signal amplification of c-H2AX foci at the site of DNA damage, the detection of c-H2AX has been identified as an early sensitive cellular biomarker of DNA damage (Nikolova et al, 2014;Rogakou et al, 1998). In this study, we developed a multi-parametric HCA assay along with the detection of c-H2AX and found that BPA and its analogues significantly altered the expression levels of c-H2AX.…”
Section: Discussionmentioning
confidence: 99%
“…There is usually a good correlation between drug doses and γ H2AX formation in vitro 23, 24. However, we observed different γ H2AX/apoptosis kinetics between fibroblasts, keratinocytes, and melanoma in the MSM that suggests a differential DNA damage response that is cell‐type dependent.…”
Section: Discussionmentioning
confidence: 63%